NTG-101: A Novel Molecular Therapy that Halts the Progression of Degenerative Disc Disease. Issue 1 (December 2018) - Matta, Ajay; Karim, Muhammad; Gerami, Hoda; Jun, Peter; Funabashi, Martha; Kawchuk, Greg; Goldstein, Alyssa; Foltz, Warren; Sussman, Marshall; Eek, Bjorn; Erwin, W.
Abstract The tremendous cost, pain and disability associated with degenerative disc disease (DDD) makes the development of a biological agent that can mitigate the course of DDD, a critical unmet need. We have identified and reported that a single injection of a combination of recombinant human (rh) Transforming growth factor beta 1 (TGF-β1) and Connective tissue growth factor (CTGF) proteins into the injured intervertebral disc (IVD) nucleus pulposus (NP) can mediate DDD in a pre-clinical rodent model. In this study, we developed and evaluated the efficacy of a novel molecular therapy (NTG-101) containing rhTGF-β1 and rhCTGF proteins suspended in an excipient solution usingin vivo models of DDD including rat-tail and chondrodystrophic (CD) canines. Needle puncture injury in CD-canine NPs resulted in loss of hydration, disc height and showed radiographic evidence of DDD like humans. However, NTG-101-injected IVDs maintained disc height and demonstrated retention of viscoelastic properties as compared to IVDs injected with phosphate buffer saline (PBS, 1X, pH = 7.2). In addition, a single intra-discal injection of NTG-101 into the injured IVD-NPs resulted in sustained expression of healthy extra-cellular matrix (ECM) proteins (aggrecan, collagen 2A1) and reduced expression of inflammation associated proteins and molecules (IL-1β, IL-6, IL-8, MMP-13, Cox-2 and PGE2) as compared to vehicle controls. In conclusion, we demonstrated that a single intra-discal injection of the novel formulation, NTG-101 confers a robust anti-inflammatory, anti-catabolic and pro-anabolic effects in pre-clinical models of DDD thereby restoring homeostasis. These findings suggest the therapeutic potential of NTG-101 for clinical use.